Safety Knowledge and Changing Behavior in Agricultural Workers: an Assessment Model Applied in Central Italy - Cecchini, Massimo; Bedini, Roberto; Mosetti, Davide; Marino, Sonia; Stasi, Serenella (Safety and Health at Work, 2018)
Background In recent years, the interest in health and safety in the workplace has increased. Agriculture is one of the human work activities with the highest risk indexes. Studies on risk perception of agricultural workers are often referred to as specific risk factors (especially pesticides), but the risk perception plays an important role in preventing every kind of accident and occupational disease. Methods The aim of this research is to test a new method for understanding the relation between risk perception among farmers and the main risk factors to which they are exposed. A secondary aim is to investigate the influence of training in risk perception in agriculture. The data collection was realized using a questionnaire designed to investigate the risk perception; the questionnaire was given to a sample of 119 agricultural workers in central Italy. Through the use of the “principal components analysis” it was possible to highlight and verify the latent dimensions underlying the collected data in comparison with scales of attitudes. Results Results show that the highest percentage of strong negative attitude is among the people who have worked for more years, while farmers who have worked for fewer years have a marked positive attitude. Conclusion The analysis of the questionnaires through the synthetic index method (Rizzi index) showed that agricultural workers involved, in particular the elderly workers, have a negative attitude towards safety; workers are hostile to safety measures if they have not attended special training courses. Agriculture is one of the human work activities with the highest risk indexes especially to pesticide.workers are hostile to safety measures if they have not attended special training courses.
Keywords: PCA; Rizzi index; agriculture; risk perception